2012
DOI: 10.1002/asi.22601
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual syntagmatic associations in user tagging

Abstract: This study aimed to integrate the linguistic theory of syntagmatic relations and the concept of topic and comment into an empirical analysis of user tagging. User tags on documents in a social bookmarking site reflect a user's views of an information object, which can augment the content description and provide more effective representation of information. The study presents a study of tag analysis to uncover semantic relations among tag terms implicit in user tagging. The objective was to identify the syntagm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This study attempts to investigate on whether syntagmatic relation and paradigmatic association can exist at the same time empirically, and tries to reveal how these two relations relate with each other. Assigned MeSH descriptors are used to represent syntagmatic relations as in (Yoon, 2012). Their paradigmatic relations are determined according to the structure of the MeSH thesaurus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study attempts to investigate on whether syntagmatic relation and paradigmatic association can exist at the same time empirically, and tries to reveal how these two relations relate with each other. Assigned MeSH descriptors are used to represent syntagmatic relations as in (Yoon, 2012). Their paradigmatic relations are determined according to the structure of the MeSH thesaurus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas paradigmatic relationships are defined a priori, as in the formal structure of an ontology, syntagmatic relationships can only be defined a posteriori, originating in the actual occurrence of terms within texts (Khoo & Na, 2006;Peters & Weller, 2008;Stock, 2010). Several studies have suggested that understanding how individuals employ syntagmatic relationships can illuminate how they classify information in online environments (Yoon 2012), create formalized structures of meaning through indexing (Olsen & Wolfram, 2008), and represent information at the conceptual level (Green, 1995b;1995c;Khoo & Na, 2006). At a basic level, syntagmatic relationships create core semantic meanings within texts via relationships between "topic," or that which the textual unit is about, and "comment," or that upon which the text elaborates (Jakobson, 1963;Yoon, 2012).…”
Section: Syntagmatic Relations In Discourse Analysismentioning
confidence: 99%
“…Several studies have suggested that understanding how individuals employ syntagmatic relationships can illuminate how they classify information in online environments (Yoon 2012), create formalized structures of meaning through indexing (Olsen & Wolfram, 2008), and represent information at the conceptual level (Green, 1995b;1995c;Khoo & Na, 2006). At a basic level, syntagmatic relationships create core semantic meanings within texts via relationships between "topic," or that which the textual unit is about, and "comment," or that upon which the text elaborates (Jakobson, 1963;Yoon, 2012). Breaking down user claims into syntagmatic topic/comment relationships provides a systematic process for analyzing how the topic being addressed may be consistent across individual reviews, yet its meaning might change subtly or develop further depending on the comments made about it.…”
Section: Syntagmatic Relations In Discourse Analysismentioning
confidence: 99%
“…Semantics techniques have been used to link social tags to a controlled vocabulary (Yi, ) and deploy tag analysis to uncover semantic relations (Yoon, ). A prominent theme is semantic tagging for aggregation and analysis.…”
Section: Introductionmentioning
confidence: 99%